Watanic Jurisprudence articulating the legitimate elements of the basic structure of the federal constitution - Wan Ahmad Fauzi, Wan Husain (International Islamic University Malaysia, 2021)
The doctrine of the basic structure of a constitution would be undisputable if those elements thereunder are clear and representing the facts of our local history, nationhood, and the principle of the rule of law. Former Chief Justice Tun Abdul Hamid Mohamad argued that the doctrine of the basic structure of a constitution introduced by the Indian Supreme Court contradicts Article 159 of the Federal Constitution and beyond the competent jurisdiction of the local courts. Hence, this article puts forward the conceptual framework of the basic structure adopted by the Federal Court in the case of Indira Gandhi to articulate those elements summed therein viewed from the watanic jurisprudence. The watanic jurisprudence analyses legal documents and sources of sovereignty based upon two philosophical worldviews; continuum and dichotomous frameworks relying upon the local legal history context and the present legal provisions of a country. Depending on a broad and purposive manner in proper linguistic, philosophic, and historical contexts of the Malaysian legal historical documents, the legitimate elements of the basic structure are the principle of sovereignty as embedded in the oath of office of the Yang di-Pertuan Agong together with the matters aggregated in Article 38(4), Article 159(5) and Article 161E. The oath of the Yang di-Pertuan Agong thus legitimizes Syariah compliance as the rule of law. The Federal Constitution of Malaysia also expressly protects its basic structure with strict conditional amendments. In conclusion, the basic structure of our Federal Constitution must be viewed from our local circumstances in compliance with the principle of constitutional supremacy and the rule of law.